The Motivation Factors Of Feminism Entrepreneurship In The Context Of Achieving The Sustainable Development (Entrepreneurship Journal for Finance and Business, 2023)
This research aims to diagnose the nature of the impact of the factors that stimulate female's entrepreneurship in sustainable development, and also aims to determine which dimensions of the factors that stimulate female's entrepreneurship are more important in achieving sustainable development. Data through a questionnaire prepared for this purpose, as the research community consisted of (684) female entrepreneurs in the Station Foundation for Entrepreneurship, which is one of the leading institutions in the field of entrepreneurship in Iraq, while the research sample included (70) female entrepreneurs from the participants in the program (Raaidat and Yanhad) in addition to co- working space in the station and in its two branches in Baghdad and Mosul, and the researcher analyzed the outputs of the questionnaire statistically and processed them through the program (SPSS Version 26).    The research reached a set of conclusions, the most prominent of which are: It was found that women are motivated to become entrepreneurs by several factors in the following order: their desire to obtain independence first, followed by their access to training, then the existence of social networks, followed by education, and finally family support. Based on the above, the researcher recommends: Women members are interested in entrepreneurship, with the need to provide support, assistance and encouragement to them, starting with listening to their ideas and providing an appropriate family environment to adopt their creative ideas, as one of the success equations for an individual is the support of his family.